2007
DOI: 10.1016/j.nurt.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid: Second Generation

Abstract: Summary:The manuscript focuses on structure-activity relationship studies of CNS-active compounds derived from valproic acid (VPA) that have the potential to become secondgeneration VPA drugs. Valproic acid is one of the four most widely prescribed antiepileptic drugs (AEDs) and is effective (and regularly approved) in migraine prophylaxis and in the treatment of bipolar disorders. Valproic acid is also currently undergoing clinical trials in cancer patients. Valproic acid is the least potent of the establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 62 publications
1
133
1
1
Order By: Relevance
“…Further studies are required to identify responsible neurotransmitters that suppress the M-current during seizures. It has been reported that some VPA metabolites, which are primarily generated in the liver (51), have more potent anticonvulsant action (52). In our case, antihyperexcitation effects were reproduced in cultured cells.…”
Section: Discussionsupporting
confidence: 61%
“…Further studies are required to identify responsible neurotransmitters that suppress the M-current during seizures. It has been reported that some VPA metabolites, which are primarily generated in the liver (51), have more potent anticonvulsant action (52). In our case, antihyperexcitation effects were reproduced in cultured cells.…”
Section: Discussionsupporting
confidence: 61%
“…Valproate has been used clinically for a long time in many neuropsychiatric disorders, and recently for HIV and cancers, in which it is used as a sensitizing agent within a polytherapy regimen [45,46]. However, valproate is a known human teratogen when administered during the first trimester of pregnancy [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…It is used mostly for the treatment of several types of seizures, bipolar disorders, various psychiatric syndromes, and migraines (Perucca, 2002;Peterson and Naunton, 2005;Bialer and Yagen, 2007). In addition, VPA has emerged recently as a drug that shows potential in cancer treatment (Duenas-Gonzalez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%